Pemikiran politik islam menurut perspektif Hasan Al-Bana dan Sayyid Quthb - Ulinnuha, Ahsin Haris (Maliki Interdisciplinary Journal, 2026)
This article examines the political thought of two influential figures in modern Islamic movements, Hasan al-Banna and Sayyid Qutb. Both played central roles in shaping the ideological foundation of the Muslim Brotherhood and contributed significantly to the rise of Islamic political consciousness in the twentieth century. This study aims to explore their intellectual backgrounds, outline their key political ideas, and analyze the similarities, differences, and contemporary relevance of their perspectives. Using a descriptive–qualitative approach based on literature review, the analysis reveals that both al-Banna and Qutb view Islam as a comprehensive system that governs all aspects of life, reject secularism, and emphasize the centrality of Sharia in social and political structures. However, their approaches differ substantially: al-Banna advocates gradual transformation through education, moral cultivation, and community development, while Qutb adopts a more ideological and confrontational stance, especially through his concepts of hakimiyyah (divine sovereignty) and modern jahiliyyah. Their ideas remain relevant in current debates on Islamic political thought, influencing both moderate reformist movements and critical perspectives on modern socio-political systems.